Enhancement of Omega-3 DHA content by Feeding Hermetia illucens and Microalgae Aurantiochytrium sp. on Catfish - Husnin Nahry Yarza; Andri Hutari; Meitiyani Meitiyani; Ranti An Nisaa; Putri Ayu Rhidailahi; Dhanti Cyntia Prameswari; Doddy Irawan Setyo Utomo (Universitas Labuhanbatu, 2025)
The growing demand for sustainable and high-quality animal feed has led to exploring alternative sources of protein and other essential nutrients. The black soldier fly (BSF) maggots Hermetia illucens and microalgae Aurantiochytrium sp. are promising candidates. Both have shown significant potential due to their nutritional profiles and environmental benefits. This study aimed to compare the fatty acid content of two groups of Sangkuriang catfish. One group was given commercial animal feed, while the other group was fed with a combination of Aurantiochytrium sp. microalga biomass feed, Hermetia illucens maggot, rice bran, and corn flour. The catfish fed with Aurantiochytrium sp. microalga biomass, Hermetia illucens maggot, rice bran, and corn flour had a different fatty acid composition than the control group. This alternative diet led to an increase in the omega-3 docosahexaenoic fatty acid (DHA) content in the catfish. The study results suggest that fish feed containing Hermetia illucens maggots and microalgae Aurantiochytrium sp. can enhance fish's beneficial nutrition after being fed this particular feed mixture.